Asymmetrical Gemini Surfactants Directed Synthesis Of Hierarchical ZSM‐5 Zeolites and Their Immobilization of Molybdenum Complex for the Catalytic Epoxidation of Alkenes. Issue 20 (6th September 2021) - Li, Pan; Li, Angxi; Ruan, Renjie; Guo, Yingxiong; He, Qian; Zou, Wenhong; Hou, Linxi
Abstract: An eco‐friendly strategy for the synthesis of highly ordered meso‐ and microporous zeolites is required both in academia and industry. Therefore, asymmetrical anionic‐nonionic gemini surfactants, polyoxyethylene laurinol ether sodium sulfoitaconate (Gemini‐ n ), have been designed, synthesized and used in the directed synthesis of hierarchical ZSM‐5 zeolites (HZSM‐5) by imparting substantial mesoporosity. The hydrothermal temperature, the amount of gemini surfactants and the crystallization time strongly affected the crystallization degree and the textural properties of the HZSM‐5. The tune of the porous size distribution (microporous to mesoporous) can be obtained by varying the number of the ethylene oxide units in the gemini surfactants. Besides, the use of these novel anionic‐nonionic gemini surfactants is an effective strategy to avoid phase‐separation. The existence of abundant hydroxyl groups on the surface of HZSM‐5 was used to immobilize molybdenum compound by the stable Mo−O bond. The complex with abundant intercrystal mesopores exhibited superior catalytic performance with high yield and selectivity for the epoxidation reactions of alkenes as compared to the conventional ZSM‐5. Moreover, the complex presented high catalytic ability after been reused for five times. Abstract : Gemini surfactants : Hierarchical ZSM‐5 obtained by dual‐templating synthesis strategy with green anionic‐nonionic gemini surfactants serves as mesoporogen. The HZSM‐5 with abundant intercrystal mesopores exhibited a superior catalytic performance for large molecular species epoxidation reactions as compared to the conventional ZSM‐5 when used as supported molybdenum catalyst.